Pengaruh Terapi Kompres Es terhadap Penurunan Intensitas Nyeri Punggung Bawah pada Pegawai Adminitrasi di Poltekkes Dr. Rusdi Medan - Riani baiduri siregar; Heri Saputra; Rudi Purwana; Ani Ramahdhani (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Low back pain, also known as low back pain, is a common condition characterized by pain or discomfort in the lower back area, which is between the lower ribs and the buttock folds. This condition can be mild to severe, and can be temporary or chronic. One of the nonpharmacological methods that is often used to reduce the intensity of pain is ice packs. Ice packs are able to provide an analgesic effect by lowering local blood flow and reducing inflammation in the area experiencing pain. This study aims to determine the effectiveness of ice packs in reducing low back pain in office administration employees. The research design uses an experimental method with a one group pre-test–post-test design approach. The research sample consisted of 25 respondents who were administrative employees at the Helvetia Health Institute. Pain intensity measurements were taken before and after the administration of ice packs to determine the effect of this therapy on low back pain. The results showed a decrease in the intensity of low back pain with an average value before treatment of 51.63 and after treatment decreasing to 38.8. Statistical analysis yielded a significance value (p) of 0.004 < 0.05, which showed that ice packs had a significant effect on reducing low back pain in administrative employees. Regular application of ice packs can be a simple, safe, and effective intervention that can be done independently at home by employees to reduce pain. This study provides recommendations for health workers to promote ice pack therapy as a non-pharmacological pain relief method, especially for office workers who often experience low back pain due to static work positions.